2021
DOI: 10.3389/fgene.2021.670582
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Detection of Copy Number Variations and Their Association With Distinct Phenotypes in the World’s Sheep

Abstract: Copy number variations (CNVs) are a major source of structural variation in mammalian genomes. Here, we characterized the genome-wide CNV in 2059 sheep from 67 populations all over the world using the Ovine Infinium HD (600K) SNP BeadChip. We tested their associations with distinct phenotypic traits by conducting multiple independent genome-wide tests. In total, we detected 7547 unique CNVs and 18,152 CNV events in 1217 non-redundant CNV regions (CNVRs), covering 245 Mb (∼10%) of the whole sheep genome. We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 71 publications
(98 reference statements)
3
25
0
Order By: Relevance
“…The proteins of the LRP1B gene (within CNVR_59, common to all breeds), participate in a wide range of physiological processes, including the regulation of lipid metabolism, neurodevelopment, and transport of nutrients and vitamins [ 52 , 53 ], but also in cell proliferation process, making it a potential candidate gene for the supernumerary nipple phenotype [ 54 ]. The KHDRBS2 gene, within the CNVR_310 with the highest variance, has been associated with fertility and reproductive traits in cattle [ 55 ], goat [ 56 ], and sheep [ 57 ]. Moreover, the FILIP1 gene (CNVR_185), reported by Salehian-Dehkordi et al [ 57 ] has been linked with fertility traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteins of the LRP1B gene (within CNVR_59, common to all breeds), participate in a wide range of physiological processes, including the regulation of lipid metabolism, neurodevelopment, and transport of nutrients and vitamins [ 52 , 53 ], but also in cell proliferation process, making it a potential candidate gene for the supernumerary nipple phenotype [ 54 ]. The KHDRBS2 gene, within the CNVR_310 with the highest variance, has been associated with fertility and reproductive traits in cattle [ 55 ], goat [ 56 ], and sheep [ 57 ]. Moreover, the FILIP1 gene (CNVR_185), reported by Salehian-Dehkordi et al [ 57 ] has been linked with fertility traits.…”
Section: Discussionmentioning
confidence: 99%
“…The KHDRBS2 gene, within the CNVR_310 with the highest variance, has been associated with fertility and reproductive traits in cattle [ 55 ], goat [ 56 ], and sheep [ 57 ]. Moreover, the FILIP1 gene (CNVR_185), reported by Salehian-Dehkordi et al [ 57 ] has been linked with fertility traits. The ACAD9 gene is a recently identified acyl-CoA dehydrogenase that demonstrates maximum activity with unsaturated long-chain acyl-CoAs [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fat tail in sheep is an adaptive response to harsh environmental conditions and is a source of energy in adverse environmental conditions such as periods of food shortage and severe cold 48 . Salehian-Dehkordi et al identified various CNV-related genes associated with climatic adaptation and artificial selection in sheep 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Salehian-Dehkordi et al using the genome-wide SNPs detected eight CNVRs associated with fat deposition in the tails in the Large-tailed and Small-tailed Han sheep horboting PPP1R11 and GABBR1 genes to be involved in fat deposition in the tails 29 . Zhu et al using high-density SNP arrays detected genome-wide CNVs in Chinese indigenous sheep with different types of tails and reported CNVRs including genes associated with fat deposition 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike SNPs, which refer to the substitution, deletion or insertion of just a single nucleotide for another, CNVs involve fragmental variation even larger than 1000 bp in size ( Iafrate et al, 2004 ; Feuk et al, 2006 ). Therefore, it has been widely recognized that CNVs have the potential to markedly affect phenotypic traits of domestic animals ( Salehian-Dehkordi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%